High‐entropy yttrium pyrochlore ceramics with glass‐like thermal conductivity for thermal barrier coating application. Issue 10 (17th June 2022) - Liu, Hu‐Lin; Pang, Sha; Liu, Chang‐Qing; Wu, Yuan‐Ting; Zhang, Guo‐Jun
Abstract: A2 B2 O7 ‐type oxides with low thermal conductivities are potential candidates for next‐generation thermal barrier coatings. The formation of high‐entropy ceramics is considered as a newly effective way to further lower their thermal conductivities. High‐entropy Y2 (Ti0.2 Zr0.2 Hf0.2 Nb0.2 Ta0.2 )2 O7 (5HEO) and Y2 (Ti0.25 Zr 0.25 Hf0.25 Ta0.25 )2 O7 (4HEO) ceramics were prepared by in situ solid reaction sintering, considering the important roles of B‐site cations on thermal conductivities of the A2 B2 O7 ‐type oxides. Reaction process, phase structures, microstructures, and thermal conductivities of the as‐sintered ceramics were investigated. Lattice distortion effects on their thermal conductivities were also discussed by using the proposed criterion based on the supercell volume difference of the individual compounds. Near fully‐dense 5HEO and 4HEO ceramics were obtained after being sintered at 1600°C. The former one had a dual‐phase structure containing high‐entropy Y2 (Ti0.227 Zr0.227 Hf0.227 Nb0.136 Ta0.182 )2 O7.318 pyrochlore oxide (5HEO‐P) and Y(Nb, Ta)O4 solid solution, while the latter one was a single‐phase pyrochlore oxide (4HEO‐P) with homogeneous element distribution. The formed 5HEO‐P oxide has larger lattice distortion than 4HEO‐P oxide due to the larger total amounts of Nb and Ta cations at B sites in the 5HEO‐P oxide. It results in lower thermal conductivity of 5HEO ceramics (keeping at 1.8 W·m –1 ·K –1 ) than those of 4HEO ceramics (ranging from 1.8 to 2.5 W·m –1 ·K –1 ) at temperatures from 25°C to 1400°C. Their glass‐like thermal conductivities were determined by the selection of B site cations and high‐entropy effects. These results provide some useful information for the material design of novel thermal barrier coating materials.